Exploring Psychological Determinants in Using Jasa Titip with an Approach of Theory of Planned Behavior and Perceived Trust - Sitanggang, Rosalina; Fachira, Ira (Universitas Negeri Semarang, 2025)
The purpose of this study is to explore Theory Planned Behavior with Perceived Trust for analyzing the behavior of consumers in the purchase decision making process of exclusive and inclusive products using jasa titip. The preliminary study determined that this service maintains the purchase of cheaper luxury products even though the local product has the same advantages. Following that, this study uses a quantitative method approach with Partial Least Square Structural Equation Modeling for the analysis data process to know about the perspective from the user of jasa titip. The result of this study confirms that attitude, subjective norms, perceived behavioral control, and perceived trust is a strong determiner from consumers while making a decision in purchasing exclusive products through the jasa titip. Thus, this study was interpreted as a theoretically and empirically studied in a new online shopping method on social media.